2021
DOI: 10.1111/jcpt.13553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist intervention in antibiotic stewardship programmes for critically ill neonates: A systematic review and meta‐analysis

Abstract: What is known and objective Antibiotic stewardship programmes (ASPs) are introduced to ensure effective antibiotic use. Pharmacists can be involved in ASPs to facilitate the appropriate antibiotic use. Prolonged use of antibiotics causes adverse events in critically ill neonates. Hence, this systematic review and meta‐analysis was aimed at investigating pharmacists’ functions in ASPs in critically ill neonates and the effect of ASP implementation on antibiotic use. Methods A comprehensive search of PubMed/Medl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Therefore, pharmacists (hospital and/or clinical) can be involved in ASPs to facilitate appropriate antibiotic use. A recent systematic review on this topic showed that involving pharmacists in ASPs reduces both the use and duration of antibiotic treatment in critically ill neonates [80,81].…”
Section: Precision Dosing and Therapeutic Monitoringmentioning
confidence: 99%
“…Therefore, pharmacists (hospital and/or clinical) can be involved in ASPs to facilitate appropriate antibiotic use. A recent systematic review on this topic showed that involving pharmacists in ASPs reduces both the use and duration of antibiotic treatment in critically ill neonates [80,81].…”
Section: Precision Dosing and Therapeutic Monitoringmentioning
confidence: 99%